Disease conditions in cats and dogs diagnosed at the Post-Mortem Laboratory of the Faculty of Veterinary Medicine, Universiti Putra Malaysia between 2005 and 2015 - Maniam, Rathiymaler; Saad, Mohd Zamri; Salleh, Annas (Universiti Putra Malaysia Press, 2017)
Keeping pets is a growing trend in Malaysia. This retrospective study involves data analysis of cases of dogs and cats submitted to the Post-Mortem Laboratory, Faculty of Veterinary Medicine, Universiti Putra Malaysia between 2005 and 2015. A total of 37 disease conditions were diagnosed among dogs with septicaemia (10.2%), mammary gland tumor (8.4%) and canine distemper (7.9%) were significantly (p<0.05) more frequently diagnosed. In cats, a total of 27 disease conditions were diagnosed with traumatic injuries (19.5%), feline infectious peritonitis (15.1%) and sporotrichosis (12%) were significantly (p<0.05) more frequent. Poor awareness among pet owners towards the health requirements of their pets is a main reason for the above.